Children and Explorations of Self-Perception: Life Stories Related to Moves Between Home and Foster Home - Bjørn Øystein Angel (Social Work & Society, 2013)
This article analyses the experiences and perceptions of ten children after relatively lengthy placements in foster homes in Norway. The purpose is to explore how stays and moves from home to foster home and back home again affects children's self-perception, consisting of personal symbols and self-esteem. The survey shows three types of change. Some children's self-perception is strengthened. The second pattern shows children whose self-perception is subdued. The last pattern shows children who do not experience any change.